(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to examine the role of internal auditing in improving financial performance within public sector institutions, through an applied study on the Social Security Fund – Western Region Branch. The research problem focused on determining the extent to which internal auditing contributes to enhancing financial performance amid the financial and administrative challenges faced by public institutions. The study adopted a descriptive-analytical approach, using a questionnaire as the main data collection tool. The questionnaire was distributed to a stratified random sample of (23) employees working at the Social Security Fund. Data were analyzed using the Statistical Package for Social Sciences (SPSS). The study reached a number of conclusions, most notably a statistically significant relationship between the efficiency and effectiveness of internal auditing and improved financial performance. The study recommended the need to activate the role of internal auditing, develop its procedures, and enhance its independence.